2012
DOI: 10.1038/ng.2443
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic analysis detects widespread gene-body DNA hypomethylation in chronic lymphocytic leukemia

Abstract: We have extensively characterized the DNA methylomes of 139 patients with chronic lymphocytic leukemia (CLL) with mutated or unmutated IGHV and of several mature B-cell subpopulations through the use of whole-genome bisulfite sequencing and high-density microarrays. The two molecular subtypes of CLL have differing DNA methylomes that seem to represent epigenetic imprints from distinct normal B-cell subpopulations. DNA hypomethylation in the gene body, targeting mostly enhancer sites, was the most frequent diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

80
579
5
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 531 publications
(673 citation statements)
references
References 42 publications
80
579
5
9
Order By: Relevance
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…22 An increasing number of reports have further proposed that the methylome-transcriptome relationship cannot be represented by a simple model when considering large, high quality datasets. 10,21,23,36,37 In these studies, positive and negative correlations between methylation alterations and transcriptome changes were found only for a minority of CpGs. It was also suggested that the relationship depends on the CpG-content of the promoter region.…”
Section: Discussionmentioning
confidence: 89%
“…Based on prior observations by us and others suggesting that (1) HCP genes and LCP genes were regulated differently 13,20,21 and (2) the effects of promoter and gene body methylation diverged, 22,23 we analyzed these scenarios separately. We identified genes that were up-or down-regulated by nerve damage and harbored dDMCs in their promoter or gene body.…”
Section: Genic Ddmcs Altered By Spinal Nerve Ligationmentioning
confidence: 99%
“…When analyzing the genomic distribution of dmCpGs and, in line with previously published reports (Cruickshanks et al., 2013; Kulis et al., 2012; Yuan et al., 2015), we found that hypomethylated CpGs were enriched at open sea DNA regions, principally intronic and intergenic, irrespective of the type of process. The distribution of hypermethylated CpGs was found to be similar to that of the array, which is to a certain extent to be expected because it was designed to interrogate a promoter‐ and CpG dense‐biased portion of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the analysis of the chromatin states, DNA hypomethylation in cancer was associated with heterochromatin DNA regions, which is in line with previous work (Berman et al., 2011; Kulis et al., 2012). In contrast, chromatin marks of DNA hypomethylation in aging were associated with enhancers, reinforcing previous observations performed with the Infinium HumanMethylation27K Beadchip platform (Day et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation has been compared between normal B-cell populations and CLL [136][137][138][139], leading to important observations. In a first report, three CLL classes were defined, based on DNA methylation patterns, which relate to naive B cells, memory B cells, and the third group being intermediate.…”
Section: Dna Methylationmentioning
confidence: 99%